Impact of the Breakdown Behavior on Chinese Traditional Stewed Pork with Brown Sauce: Physical Properties Using Microstructural Analysis - Han, Yaohui; Gong, Ana; Deng, Yajun; Liu, Dengyong; Wang, Hui-Min (Journal of food quality, 2017)
The potential physics differences of Chinese traditional stewed pork during mastication were investigated. Ten subjects chewed and expectorated the fat and lean layers of stewed pork with brown sauce at different stages of mastication. The produced boluses were analyzed for their physical properties. The results suggested the subjects’ saliva secretion and moisture content of the boluses during mastication increased significantly depending on subjects and food types studied (P<0.05) and led to increase of bolus apparent particle size because of saliva uptake. Bolus first peak force tended to decrease significantly, whereas bolus flowability increased significantly during mastication (P<0.05). Further, microstructure of boluses revealed series processing was conducted by comminution, aggregation, hydration, and dilution. The boluses ready-to-swallow possessed a higher flowability and a homogenetic matrix. Therefore, the changes in physics and microstructure of bolus contributed to dynamic texture perception of traditional Chinese stewed pork with brown sauce.